Pilgrim Mementoes from the Holy Land: Production, Iconography, Use, and Distribution - Rosenthal-Heginbottom, Renate (Actual Problems of Theory and History of Art, 2017)
With the growing number of Christian pilgrims visiting the Holy Land the demand for sacred and magical mementoes rose. Local workshops were established, where craftsmen produced flasks and spouted juglets, bread stamps, and tokens. Mostly made of clay, they were cheap keepsakes produced and sold at and near shrines and sanctuaries. The subjects depicted are related to the sites and drawn from images at the holy places. The class documented best are flasks, including moulds; it is possible to define five distinct stylistic and iconographic groups. In imagery and elements of decoration they combine characteristic features of the Byzantine visual arts prevalent in the Holy Land. The find-spots indicate that such objects were not primarily acquired by pilgrims visiting Holy Land sites. Rather, they were sold to local pilgrims at the holy sites and the local population acquired them for household use out of private devoutness on a regular basis. Probably they were low-priced cousins of the metal ampullae in the style of the widely exported Monza/Bobbio flasks.